Anatomy of The Anatomy of Racial Inequality - Raphael, Steven (Journal of Economic Literature, 2002)
In this review, I summarize and offer thoughts about two arguments key to Glenn Loury's analysis of the anatomy of racial inequality. The first concerns the idea that many negative stereotypes held about blacks in the United States are self-fulfilling, despite little evidence of inherent differences between the races in human potential. The second argument concerns the proposition that the racial stigmatization of blacks is deeply embedded in the public consciousness and that such stigma racially biases socially cognitive processes to the severe detriment of African-Americans.